High‐contiguity genome assembly of the chemosynthetic gammaproteobacterial endosymbiont of the cold seep tubeworm Lamellibrachia barhami. (24th July 2020) - Breusing, Corinna; Schultz, Darrin T.; Sudek, Sebastian; Worden, Alexandra Z.; Young, Curtis Robert
Abstract: Symbiotic relationships between vestimentiferan tubeworms and chemosynthetic Gammaproteobacteria build the foundations of many hydrothermal vent and hydrocarbon seep ecosystems in the deep sea. The association between the vent tubeworm Riftia pachyptila and its endosymbiont Candidatus Endoriftia persephone has become a model system for symbiosis research in deep‐sea vestimentiferans, while markedly fewer studies have investigated symbiotic relationships in other tubeworm species, especially at cold seeps. Here we sequenced the endosymbiont genome of the tubeworm Lamellibrachia barhami from a cold seep in the Gulf of California, using short‐ and long‐read sequencing technologies in combination with Hi‐C and Dovetail Chicago libraries. Our final assembly had a size of 4.17 MB, a GC content of 54.54%, 137X coverage, 4153 coding sequences, and a CheckM completeness score of 97.19%. A single scaffold contained 99.51% of the genome. Comparative genomic analyses indicated that the L. barhami symbiont shares a set of core genes and many metabolic pathways with other vestimentiferan symbionts, while containing 433 unique gene clusters that comprised a variety of transposases, defence‐related genes and a lineage‐specific CRISPR/Cas3 system. This assembly represents the most contiguous tubeworm symbiont genome resource to date and will be particularly valuable for future comparative genomic studies investigating structural genome evolution, physiological adaptations and host‐symbiont communication in chemosynthetic animal‐microbe symbioses.